Non-interest (Islamic) liquidity management in the Nigerian non-interest banking: a legal study from the experience of Malaysia - Olayemi, Abdul Azeez Maruf; Hasan, Aznan; Ibrahim, Uzaimah; Buang, Ahmad Hidayat (CLJ Law Network, 2015)
One of the major potential challenges before the nascent non-interest (Islamic) banking product in Nigeria is the absence of adequate and viable Shariah-compliant instruments of liquidity management. The availability of the instrument is a sine qua non in the banking system. Conversely, Malaysia being the global hub of the Islamic banking and finance has successfully developed viable instruments for the management of Islamic liquidity. The Malaysian instruments are comparably in juxtaposition with that of the conventional system in terms of sophistication and development. The article advocates for the adoption and adaptation of the Malaysian model of Islamic liquidity management instruments into the Nigerian banking system as a panacea. The research is a qualitative comparative legal study. It aims at proposing solution to the lingering problem of non-interest liquidity management in the Nigeria nascent non-interest banking product.